Exploring the Integration of Artificial Intelligence in English as a Foreign Language Education in Indonesia - Rahman, Muhammad Arinal (Jurnal Pedagogy, 2024)
The use of AI tools in EFL teaching is growing in Indonesia, but their implementation and impact are not fully understood. This research explores how English as a Foreign Language (EFL) instructors in Indonesia integrate artificial intelligence (AI) technology into their teaching, their views on the efficacy of these tools, and the obstacles they face. Five EFL teachers in Indonesia were interviewed using a qualitative approach through semi-structured interviews. Analysis of the data showed that educators use AI tools such as Grammarly, Google Translate, ChatGPT, and Claude AI to offer feedback, assist in understanding, and create content. These tools were considered to be beneficial for enhancing students' writing abilities and enthusiasm, although worries were expressed regarding excessive dependence, academic integrity, and the possibility of obstructing critical thinking and genuine learning. Obstacles involved restrictions on tools, technological setup, and preparedness of students. The research underscores the advantages of using AI tools in EFL teaching and stresses the importance of a fair and evaluative method of incorporating them. Teachers should encourage constructivist instructional techniques to stimulate cognitive involvement and digital proficiency, guaranteeing that AI resources complement rather than substitute genuine learning. Future study on moral and educational impacts are advised.